Pengaruh Kualitas Informasi, Kualitas Sistem, Dan Kualitas Layanan Terhadap Minat Beli Ulang Pengguna Marketplace Situs Shopee (Studi Kasus Mahasiswa Kota Malang) - Mohammad Hasby Ashshiddiqi; Achmad Agus Priyono; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the relationship between information quality, system quality, and service quality on the repurchase intention of marketplace users on the Shopee site. This study used a study on Malang city students where the data was obtained by distributing questionnaires via the g-form to Malang city students who were selected by purposive sampling. Determining the number of samples in this study used the Malhotra formula and the results obtained were 90 respondents. The analytical method used in this study is instrument test (validity test, reliability test), normality test, classical assumption test (multicollinearity test, heteroscedasticity test), multiple linear regression analysis, hypothesis testing (F test and t test), coefficient of determination test. (Adjusted R2) data processing using the IBM SPSS 24 program. The results of this study indicate that information quality, system quality, and service quality simultaneously influence repurchase intention, information quality partially influences repurchase intention, system quality partially influences repurchase intention, service quality has a partial effect on repurchase intention. Keywords: information quality, system quality, service quality, repurchase intention